Poly(I:C)-exposed zebrafish shows autism-like behaviors which are ameliorated by fabp2 gene knockout - Wu, Jing; Lin, Xueting; Wu, Dian; Yan, Binhong; Bao, Mengyi; Zheng, Peilei; Wang, Jiangping; Yang, Cuiwei; Li, Zhongxia; Jin, Xiaoming; Jiang, Kewen (Frontiers in Molecular Neuroscience, 2023)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders mainly representing impaired social communication. The etiology of ASD includes genetic and environmental risk factors. Rodent models containing ASD risk gene mutations or environmental risk factors, such as exposure to maternal inflammation, show abnormal behavior. Although zebrafish conserves many important brain structures of humans and has sophisticated and fine behaviors in social interaction, it is unknown whether the social behaviors of their offspring would be impaired due to exposure to maternal inflammation. Here we reported that maternal immune activation (MIA) offspring born to mothers injected with polyinosinic:polycytidylic acid (poly(I:C)) exhibited impaired social approach and social cohesion that mimicked human ASD phenotypes. Both maternal exposure and direct embryo exposure to poly(I:C) resulted in activations of the innate immune system through toll-like receptors 3 and 4. RNA-sequencing results from MIA brain tissues illustrated that the numbers of overexpressed genes were significantly more than that of underexpressed genes. GO and KEGG analyses found that MIA-induced differential expression genes were mainly concentrated in complement and coagulation cascade pathways. PPI network analyses suggested that villin-1 (vil1) pathway might play a key role in MIA-induced ASD. Knockout of fatty acid-binding protein 2 (fabp2) in F0 zebrafish rescued the social behavior deficits in MIA offspring. Overall, our work established an ASD model with assessable behavior phenotype in zebrafish and provided key insights into environmental risk factor in ASD etiology and the influence of fabp2 gene on ASD-like behavior.